A Brief Review on Equation of Motion of Variable Mass System - Vippala, Veera (Indonesian Journal Publisher, 2025)
Newton’s second law states that the external force acting on a system is equal to the rate of change of its linear momentum. It is Galilean invariant when the system mass is constant. There is a misunderstanding that Newton’s second law is neither a valid expression nor Galilean invariant in case of variable mass system. In a variable mass system, total system mass is a still remaining constant but remnant and ejected masses vary with time at equal rates. In case of rocket, system total mass always constant but remnant mass decreasing with time and ejected mass is increasing with time at equal rates. In the existing literature equation of motion of variable system considered as equation of motion of present remnant mass. In this work we consider total mass, remnant mass and ejected mass are three different systems and Newton's law validity and its Galilean invariance are verified for these three systems.